Self-organisation in the human visual system—Visuo-motor processing with congenitally abnormal V1 input - Wolynski, Barbara; Kanowski, Martin; Meltendorf, Synke; Behrens-Baumann, Wolfgang; Hoffmann, Michael B. (Neuropsychologia, 2010)
▶ Despite abnormal V1 input, normal hit rates in a visuo-motor task in human albinism. ▶ Abnormal lateralisation patterns not only in V1, but also in higher visual areas. ▶ Largely normal lateralisation patterns in motor and somatosensory cortices. ▶ Abnormal visual representation integrated for motor processing with normal motor cortex. Due to an abnormal projection of the temporal retina the albinotic primary visual cortex receives substantial input from the ipsilateral visual field. To test whether representation abnormalities are also evident in higher tier visual, and in motor and somatosensory cortices, brain activity was measured with fMRI in 14 subjects with albinism performing a visuo-motor task. During central fixation, a blue or red target embedded in a distractor array was presented for 250ms in the left or right visual hemifield. After a delay, the subjects were prompted to indicate with left or right thumb button presses the target presence in the upper or lower hemifield. The fMRI responses were evaluated for different regions of interest concerned with visual, motor and somatosensory processing and compared to previously acquired data from 14 controls. The following results were obtained: (1) in albinism the hit rates in the visuo-motor task were indistinguishable from normal. (2) In area MT and the intraparietal sulcus there was an indication of abnormal lateralisation patterns. (3) Largely normal lateralisation patterns were evident in motor and somatosensory cortices. It is concluded that in human albinism, the abnormal visual field representation is made available for visuo-motor processing with a motor cortex that comprises an essentially normal lateralisation. Consequently, specific adaptations of the mechanisms mediating visuo-motor integration are required in albinism.